The complementarity and similarity of magnetorelaxometry and thermal magnetic noise spectroscopy for magnetic nanoparticle characterization. (1st February 2017) - Leliaert, J; Eberbeck, D; Liebl, M; Coene, A; Steinhoff, U; Wiekhorst, F; Van Waeyenberge, B; Dupré, L
Abstract: Magnetorelaxometry and thermal magnetic noise spectroscopy are two magnetic characterization techniques enabling one to estimate the magnetic nanoparticle hydrodynamic size distribution. Both techniques are based on the same physical principle, i.e. the thermal fluctuations of the magnetic moment. In the case of magnetorelaxometry these fluctuations give rise to a relaxing magnetic moment after an externally applied magnetic field is switched off, whereas thermal magnetic noise spectra are measured in the absence of any external excitation. Hence, thermal magnetic noise spectroscopy is an equilibrium measurement technique. Here, we compare the similarity and complementarity of both methods and conclude that, for particles within both methods' sensitivity range, they give the same estimate for the size distribution. For small particles (or samples with low viscosities), the used setup is not sufficiently sensitive to accurately estimate the size distribution from the relaxometry signal whereas this is still possible with thermal magnetic noise spectroscopy. For larger particles, however, magnetorelaxometry is the preferred method because of its higher signal to noise ratio and faster measurement time.